IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS PROYEK MADING UNTUK MENINGKATKAN LITERASI PADA SISWA KELAS V SDK WOLOKOLI - Chatarina; Laksana, Dek Ngurah Laba; Lawe, Yosefina Uge; Awe, Ermelinda Yosefa (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
This study aims to determine the increase in literacy of fifth grade students of SDK Wolokoli through the implementation of PBL by applying a wall magazine. This type of research uses Classroom Action Research (CAR) with a research design from Kemmis and McTaggart which consists of four stages, namely: planning, implementation of actions, observation, and reflection. This reflection is the basis for refining the actions carried out in the next cycle. The subjects in this study were fifth grade students of SDK Wolokoli with a total of 11 students consisting of 7 female students and 3 male students. Data collection techniques were carried out through observation, interviews and written texts. The instruments used included student activity observation sheets, interview guidelines, and test questions to measure the achievement of student learning outcomes. Based on the results of data analysis in cycle 1, it showed that the average student learning outcomes were 65.45 with a completeness presentation of 65.45% with a classical completeness presentation of 36.36%, and the classification criteria were in the sufficient category (not yet complete). Meanwhile, the results of data analysis in cycle II showed an average learning outcome of 78.18 with a classical completion percentage of 81.81% and the classification criteria were in the good category (complete). Based on the results of the data analysis, the study was declared successful because the classical completion of 70% of student learning outcomes met good criteria. Through the wall magazine making activity, students not only learned actively, but also showed a greater interest in learning. This study concluded that wall magazine project-based learning was effective in improving student literacy and could be implemented in other schools as a fun and useful alternative method.